Frictional analysis of deep-groove ball bearings with varying circumference radial preloads - Wang yu Chao; He yuan Xin; Weng Wei; Liu jia Rong (Advances in Mechanical Engineering, 2017)
Circumference radial preload due to the interference fit is of a great significant influence on rolling frictional power loss of bearing and service life of machinery. In this article, an analytical method where circumference radial preload is first involved is presented for determining the value of rolling friction power loss of ball bearing (SKF-6205). The experiments under different operating conditions for the bearing were carried out which verify the validity of our proposal. The work described in this article can be regarded as a foundation for the accuracy thermal modeling and friction power loss analysis of the deep-groove ball bearings in machinery.